Relación ciudadselva en la ciudad de Francisco de Orellana en su periurbanidad siendo el Referente Proyectual principal un Urbanismo Ecológico - Quevedo Narváez, Karina Elizabeth (2018)
Abstract:Among several themes, issues and problems that mark today s debate on so-called Amazonian urbanism (Becker 1995, Juan Carlos Ramírez J. - Cepal 2013), the theme of the project about the vast and blurred transition territories between the urbanized spaces and Jungle, represents one of the most interesting and complex declensions of the concept of per urbanity , as well as this has been redefined in the last 20. This peri-urban study will have an approach of two basic scales, of which we will mark the relevant interpretation for the formulation of a hypothesis that determines and promotes the development of proposals in these hybrid areas. As the expected result is to redefine the relationship between the city and the jungle, taking care about the particular characteristics of the interface between the production processes of the city and the jungle and its sequences, by deriving existing spatial prototypes towards new settlement patterns that contain new ecologies, economies, public spaces, shared or semi-public.